Pharmacodynamics of zoliflodacin plus doxycycline combination therapy against Neisseria gonorrhoeae in a gonococcal hollow-fiber infection model - Jacobsson, Susanne; Golparian, Daniel; Oxelbark, Joakim; Kong, Fabian Y. S.; Da Costa, Renata Maria Augusto; Franceschi, Francois; Brown, David; Louie, Arnold; Drusano, George; Unemo, Magnus (Frontiers in pharmacology, 2023)
Antimicrobial resistance in the sexually transmitted bacterium Neisseria gonorrhoeae is compromising the management and control of gonorrhea globally. Optimized use and enhanced stewardship of current antimicrobials and development of novel antimicrobials are imperative. The first in class zoliflodacin (spiropyrimidinetrione, DNA Gyrase B inhibitor) is a promising novel antimicrobial in late-stage clinical development for gonorrhea treatment, i.e., the phase III randomized controlled clinical trial ( ClinicalTrials.gov Identifier: NCT03959527) was recently finalized, and zoliflodacin showed non-inferiority compared to the recommended ceftriaxone plus azithromycin dual therapy. Doxycycline, the first-line treatment for chlamydia and empiric treatment for non-gonococcal urethritis, will be frequently given together with zoliflodacin because gonorrhea and chlamydia coinfections are common. In a previous static in vitro study, it was indicated that doxycycline/tetracycline inhibited the gonococcal killing of zoliflodacin in 6-h time-kill curve analysis. In this study, our dynamic in vitro hollow-fiber infection model (HFIM) was used to investigate combination therapies with zoliflodacin and doxycycline. Dose–range experiments using the three gonococcal strains WHO F (susceptible to relevant therapeutic antimicrobials), WHO X (extensively drug-resistant, including ceftriaxone-resistant; zoliflodacin-susceptible), and SE600/18 (zoliflodacin-susceptible strain with GyrB S467N substitution) were conducted simulating combination therapy with a single oral dose of zoliflodacin 0.5–4 g combined with a doxycycline daily oral dose of 200 mg administered as 100 mg twice a day, for 7 days (standard dose for chlamydia treatment). Comparing combination therapy of zoliflodacin (0.5–4 g single dose) plus doxycycline (200 mg divided into 100 mg twice a day orally, for 7 days) to zoliflodacin monotherapy (0.5–4 g single dose) showed that combination therapy was slightly more effective than monotherapy in the killing of N. gonorrhoeae and suppressing emergence of zoliflodacin resistance. Accordingly, WHO F was eradicated by only 0.5 g single dose of zoliflodacin in combination with doxycycline, and WHO X and SE600/18 were both eradicated by a 2 g single dose of zoliflodacin in combination with doxycycline; no zoliflodacin-resistant populations occurred during the 7-day experiment when using this zoliflodacin dose. When using suboptimal (0.5–1 g) zoliflodacin doses together with doxycycline, gonococcal mutants with increased zoliflodacin MICs, due to GyrB D429N and the novel GyrB T472P, emerged, but both the mutants had an impaired biofitness. The present study shows the high efficacy of zoliflodacin plus doxycycline combination therapy using a dynamic HFIM that more accurately and comprehensively simulate gonococcal infection and their treatment, i.e., compared to static in vitro models, such as short-time checkerboard experiments or time-kill curve analysis. Based on our dynamic in vitro HFIM work, zoliflodacin plus doxycycline for the treatment of both gonorrhea and chlamydia can be an effective combination.